1995
DOI: 10.1518/001872095779049462
|View full text |Cite
|
Sign up to set email alerts
|

Situation Awareness and the Cognitive Management of Complex Systems

Abstract: The issue of how to support situation awareness among operators of complex systems or vehicles is a growing concern in a number of industries, especially when automation takes the operators partly "out of the loop." Cognitive theory suggests that comprehension of the flow of events is an active process, constrained by the dynamics and modularity of attention and memory. Focusing on issues of commercial aviation, we review the meaning of the term situation awareness both definition ally and by way of examples. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
162
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(167 citation statements)
references
References 20 publications
1
162
0
4
Order By: Relevance
“…Endsley (1995) Current SA theories show that SA assessment is influenced by individual, task and system factors. Operators' abilities, attention, working memory capacity, experience, level of training, information processing mechanisms, goals specific to their needs, and expectations are considered as influential individual factors (Adams et al, 1995;Durso and Sethumadhavan, 2008;Endsley, 1995;Patrick and Morgan, 2010). Task complexity, stress, workload and automation are considered as task factors which influence SA assessment (Endsley, 1995;Kaber et al, 2006;Wickens, 2002).…”
Section: Sa Assessmentmentioning
confidence: 99%
“…Endsley (1995) Current SA theories show that SA assessment is influenced by individual, task and system factors. Operators' abilities, attention, working memory capacity, experience, level of training, information processing mechanisms, goals specific to their needs, and expectations are considered as influential individual factors (Adams et al, 1995;Durso and Sethumadhavan, 2008;Endsley, 1995;Patrick and Morgan, 2010). Task complexity, stress, workload and automation are considered as task factors which influence SA assessment (Endsley, 1995;Kaber et al, 2006;Wickens, 2002).…”
Section: Sa Assessmentmentioning
confidence: 99%
“…The view of SA as a product or process has important implications for its operational definition and its measurement. Yet another view is taken by researchers who emphasise the interrelationship between product and process in postulating that the current mental representation affects the process of acquiring and interpreting new information in an on-going cycle (e.g., Adams, Tenney, & Pew, 1995, by referring to Neisser's perceptual cycle). This view of SA as interrelated product and process is hold in this work.…”
Section: What Is Situation Awareness?mentioning
confidence: 99%
“…This situation model is dynamic in the sense that it has to be continuously updated through the alternation of top-down and bottom-up attentional processes (Adams et al, 1995;Baumann & Krems, 2007;Durso et al, 2007;Endsley, 1995bEndsley, , 2000b. The construction of the situational model is based on the perception of new elements in the environment which are then integrated into a coherent mental representation by means of pattern recognition (Durso & Gronlund, 1999;Durso et al, 2007).…”
Section: The Role Of Top-down and Bottom-up Attentional Processes In mentioning
confidence: 99%
See 1 more Smart Citation
“…Other approaches have been suggested that emphasize the dynamic nature of this process. For example, one approach that emphasizes the dynamic nature of SA is the use of the perception/action cycle (Adams, Tenney, & Pew, 1995). Figure 2 shows that the perception/action cycle consists of three elements: (a) the object (i.e., available information in the external environment); (b) the schema (i.e., internal knowledge that is theoretically structured in an organized manner, developed through training/experience, and is stored in long-term memory when not in use); and (c) exploration (i.e., a search of the environment by the observer).…”
Section: Information-processing Modelsmentioning
confidence: 99%